2023
DOI: 10.3390/toxins15010074
|View full text |Cite
|
Sign up to set email alerts
|

Highly Evolvable: Investigating Interspecific and Intraspecific Venom Variation in Taipans (Oxyuranus spp.) and Brown Snakes (Pseudonaja spp.)

Abstract: Snake venoms are complex mixtures of toxins that differ on interspecific (between species) and intraspecific (within species) levels. Whether venom variation within a group of closely related species is explained by the presence, absence and/or relative abundances of venom toxins remains largely unknown. Taipans (Oxyuranus spp.) and brown snakes (Pseudonaja spp.) represent medically relevant species of snakes across the Australasian region and provide an excellent model clade for studying interspecific and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…The scope of our study was on interspecific relationships between venom complexity and diet diversity, such that by controlling for intraspecific variation, we consider macroevolutionary patterns of venom evolution rather than relationships between populations within a species. Although intraspecific studies of venom variation are vital to our understanding of venom evolution [2,28], our study has a different focus and cannot address questions related to how individual snake venoms are related to the diets of individual snakes.…”
Section: Discussionmentioning
confidence: 99%
“…The scope of our study was on interspecific relationships between venom complexity and diet diversity, such that by controlling for intraspecific variation, we consider macroevolutionary patterns of venom evolution rather than relationships between populations within a species. Although intraspecific studies of venom variation are vital to our understanding of venom evolution [2,28], our study has a different focus and cannot address questions related to how individual snake venoms are related to the diets of individual snakes.…”
Section: Discussionmentioning
confidence: 99%
“…Venom variation in snakes can be observed on the interspecific level (between species) and intraspecific level (within a species) [ 9 ]. While venom variation between species has been well studied (e.g., [ 4 , 5 , 10 , 11 ]), the extent of intraspecific variation is starting to gain significant attention [ 12 ]. A thorough understanding of venom variation is of interest to different scientific disciplines, as venom variation provides a model system for understanding adaptive responses to biotic and abiotic factors in an ecological context [ 5 , 7 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The current main drawback in this analytical workflow is the tedious manual integration of all peak areas found in each venom analysed. In one of our previous studies, a similar workflow was demonstrated with venoms of Australian elapids for which the LC-MS data was indeed labouriously integrated manually (and the HT venomics results were not included) [ 10 ]. This drawback of manually integrating the intensities of all toxin m / z values found for each venom (and in this endeavour, only considering the highest charge state per toxin) is illustrated by the many months it took to process all LC-MS data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudonaja textilis is the second most lethal terrestrial venomous snake in the world, based upon murine models of toxicity (Broad et al 1979), and is responsible for the majority of snakebite deaths in eastern Australia (Sutherland 1992; White 2009). Venom gland transcriptomics and venom proteomics have been used to profile P. textilis venom composition (Birrell et al 2006; Viala et al 2015; Reeks et al 2016), and studies have documented geographic, seasonal, ontogenetic, and individual venom variation (Williams and White 1992; Flight et al 2006; Skejić and Hodgson 2013; Skejić et al 2015; Jackson et al 2016; McCleary et al 2016; van Thiel et al 2023). Using high-throughput transcriptomics, we evaluated P. textilis mRNAs and microRNAs (miRNAs) in a Milked Venom Gland (MVG) and Unmilked Venom Gland (UVG) from an individual snake, eliminating contributing factors involved in venom variation, to identify mechanisms regulating toxin expression.…”
Section: Introductionmentioning
confidence: 99%